PERANCANGAN SISTEM PALANG PINTU OTOMATIS TERPILIH BERBASIS RFID - Charisma Dwilestari; Agustinus Purna Irawan; Agus Halim (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
An apartment is a place to live in a building, equipped with various facilities, and is a public area inhabited by hundreds or even thousands of people. The security system in the apartment is not comfortable and safe, because of the condition of the apartment area that can be accessed by anyone as a fellow occupant (one area but in a different building). Based on the observations that have been made, one solution that can be done is to limit access to the apartment building. This access restriction can be done by dividing the entrance and adding boom barriers in each lane. The method used is a design method based on the results of observations. The design of this system considers the number of lanes, vehicle speed, and distance traveled. The speed used is in the range of 5 km/h and 20 km/h with a maximum distance of 27,081 m and a minimum distance of 9.998 m. The fastest travel time obtained is 1.799 s with a speed of 20 km/h and the slowest is 19.497 s with a speed of 5 km/h.